Introduction of active and passive control options for hydrostatic pressure chambers - Tóth, Sándor Gergő; Takács, György (Design of Machines and Structures, 2020)
One of the critical points in the design of hydrostatic bearings is the proper selection of the pressure control of the bearing recess, yet the design methods do not pay much attention to this. In addition to conventional solutions, the control of the pressure recesses can be accomplished by the use of volumetric and pressure-sensitive valves in the hydraulics to achieve greater bearing stiffness. A new way of regulating can also be the regulation of the recess with proportional valves.